1997
DOI: 10.1038/sj.leu.2400572
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cytosine arabinoside and etoposide: an effective regimen without anthracyclines for refractory childhood acute non-lymphocytic leukemia

Abstract: The purpose of this report is to describe the tolerability and poside at 1200 mg/m 2 , in children with relapsed and refracactivity of the combination of high-dose cytosine arabinoside tory acute leukemias. Ara-C, daunorubicin, etoposide, thioguanine and dexame-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…However, intensive regimens with or without anthracyclines appeared similarly effective, and this has important implications for the avoidance of cardiotoxicity in children with high cumulative exposure to anthracyclinescardiotoxicity was a cause of morbidity and mortality in AML 10 where children received 300 mg/m 2 of daunorubicin and 50 mg/m 2 of mitoxantrone, 3 and avoidance of further anthracyclines and/or strategies for cardioprotection should be employed wherever possible. Survival rates of 20-40% have been reported in selected patients receiving consolidation with intensive chemotherapy, ABMT or BMT in second remission, [17][18][19][22][23][24][25][26][27][28] and similar outcomes were observed both in this study, and by the BFM group. 7 Children who received chemotherapy alone in our study had significantly shorter first remissions than those treated by BMT, and 11/18 of this group relapsed again or died of toxicity prior to the median time to transplant indicating selection bias between treatment groups.…”
Section: Figuresupporting
confidence: 75%
“…However, intensive regimens with or without anthracyclines appeared similarly effective, and this has important implications for the avoidance of cardiotoxicity in children with high cumulative exposure to anthracyclinescardiotoxicity was a cause of morbidity and mortality in AML 10 where children received 300 mg/m 2 of daunorubicin and 50 mg/m 2 of mitoxantrone, 3 and avoidance of further anthracyclines and/or strategies for cardioprotection should be employed wherever possible. Survival rates of 20-40% have been reported in selected patients receiving consolidation with intensive chemotherapy, ABMT or BMT in second remission, [17][18][19][22][23][24][25][26][27][28] and similar outcomes were observed both in this study, and by the BFM group. 7 Children who received chemotherapy alone in our study had significantly shorter first remissions than those treated by BMT, and 11/18 of this group relapsed again or died of toxicity prior to the median time to transplant indicating selection bias between treatment groups.…”
Section: Figuresupporting
confidence: 75%
“…Etoposide and AraC Lesions Stimulate DNA Cleavage Mediated by Human Topoisomerase II␣ in an Additive or Synergistic Fashion-Chemotherapeutic regimens that combine araC with etoposide display synergistic effects in murine leukemia models and are used routinely for the treatment of patients with relapsed or refractory acute leukemias (1,57,58). Although abasic lesions dominate over etoposide and negate the enhancement of topoisomerase II-mediated DNA cleavage by the drug (not shown) (27), DNA distortions induced by the inclusion of an arabinose ring differ from those that accompany base loss (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Resultsmentioning
confidence: 99%
“…These patients also tend to have higher incidences of fungal infections and mucositis. 25,26 A very recent study has suggested that delays in securing a matched donor may be circumvented if enhanced GVHD prophylaxis (albeit, without ex vivo T cell depletion) is offered and a haplo-identical-related donor is used without increasing the outcomes of acute or chronic GVHD. 27 Satisfactory antileukemic effects have long been described for TBI, in combination with piperazinedione, in adults with primary refractory acute leukemia in a series of reports.…”
Section: Discussionmentioning
confidence: 99%